The effect of criminal identity on dishonesty - Alain Cohn; Michel André Maréchal; Thomas Noll (University of Zurich, Department of Economics, 2013)
We conducted an experiment with 182 inmates from a maximum-security prison to analyze the impact of criminal identity on dishonest behavior. We randomly primed half of the prisoners to increase the mental saliency of their criminal identity, while treating the others as the control group. The results demonstrate that prisoners become more dishonest when we render their criminal identity more salient in their minds. An additional placebo experiment with regular citizens shows that the effect is specific to individuals with a criminal identity. Moreover, our experimental measure of dishonesty correlates with inmates' offenses against in-prison regulation. Altogether, these findings suggest that criminal identity plays a crucial role in rule violating behavior.
Keywords: K00; C93; K14; K42; Z10; 330; Dishonesty; Identity; Crime; Prison; Experiment